Questions on diaspora: hybridism, identity and borders – a study on Leslie Marmon Silko’s Ceremony - Guanaes, Alvany Rodrigues Noronha (ITINERÁRIOS – Revue de Littérature, 2008)
The diversity of migratory displacements has opened space to new views on the concept of diaspora, often associated with the Jewish dispersion. Multiple transnational movements have disclosed extensive inquiries into aspects of migratory phenomena, mainly after decolonization processes. Peoples from ex-colonies have come to their “mother land” in search for better social and economical status. Nevertheless, at their new home, they come upon a dystopia which forces them to contend against barriers to their inclusion in this new society and to face situations on which their own identity and sense of belonging are under consideration. Therefore, the concept of hybridism is investigated on this paper, aiming to discuss the positioning of these disrupted individuals on an arena of cultural tension. This paper, however, goes further on theories of dispersion to include the Native Americans as a historically diasporic group in their own homeland. Leslie Marmon Silko’s first novel Ceremony is the background to discuss the fundamental theories of borders, cultural encounters and hybridism, whose influences on the construction of displaced peoples’ cultural identity shed light on the reasons why a broader interpretation of the term diaspora is to be taken into account.